2021
DOI: 10.1016/j.ajog.2020.12.781
|View full text |Cite
|
Sign up to set email alerts
|

758 Hypertensive disease of pregnancy (HDP) among high risk women with stage 1 hypertension

Abstract: per week and 91 were in the top 90th percentile (High ASB), consuming >21 ounces per week. Sixty percent of the cohort consumed no ASB. Demographic characteristics were similar between groups. No significant differences were found for primary or secondary outcomes after adjusting for potential confounding variables. CONCLUSION: Most patients consumed some SSB, no ASB, and there were no differences in pregnancy outcomes between the highest consumers in both groups. Beverage consumption is an important aspect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For women with pre-existing DM, pre-eclampsia developed in 18% of those receiving aspirin compared to 22% in the placebo group (P = 0.38; relative risk 0.9 (0.6-1.2)). 24 Testani et al 25 reported a sub-analysis of this same dataset of women in a published conference abstract. Participants with pre-existing DM with stage 1 hypertension defined as systolic blood pressure (BP) 130-139 mmHg or diastolic BP 80-89 mmHg (2017 American College of Cardiology/American Heart Association (ACC/AHA) Hypertension Guidelines 26 ), compared to those normotensive in early pregnancy, had a relative risk of developing a hypertensive disease of pregnancy (defined here as gestational HT, pre-eclampsia, and pre-eclampsia with severe features) of 2.4 (95% CI 1.6-3.5; P < 0.05) if randomised to placebo, and 1.1 (95% CI 0.6-1.7) if randomised to aspirin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For women with pre-existing DM, pre-eclampsia developed in 18% of those receiving aspirin compared to 22% in the placebo group (P = 0.38; relative risk 0.9 (0.6-1.2)). 24 Testani et al 25 reported a sub-analysis of this same dataset of women in a published conference abstract. Participants with pre-existing DM with stage 1 hypertension defined as systolic blood pressure (BP) 130-139 mmHg or diastolic BP 80-89 mmHg (2017 American College of Cardiology/American Heart Association (ACC/AHA) Hypertension Guidelines 26 ), compared to those normotensive in early pregnancy, had a relative risk of developing a hypertensive disease of pregnancy (defined here as gestational HT, pre-eclampsia, and pre-eclampsia with severe features) of 2.4 (95% CI 1.6-3.5; P < 0.05) if randomised to placebo, and 1.1 (95% CI 0.6-1.7) if randomised to aspirin.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Caritis et al, 30 which represents the largest single study that included women with DM, used the relatively low dose of 60 mg aspirin daily commencing at a relatively late gestation of 13-26 weeks, two possible contributing factors to their non-significant result. Additionally, the varied preeclampsia risk in women with DM may be affected by diabetes type, disease progression or presence of comorbidities, with Testani et al 25 demonstrating that women with DM with stage 1 hypertension have more than double the risk of pre-eclampsia compared to normotensive women with DM. The severity of diabetes, baseline glycaemic control and presence of comorbidities including chronic kidney disease, is likely to have an impact on pre-eclampsia outcome; however, this information is unknown for the women with DM reported in the published RCTs to date.…”
Section: Main Findingsmentioning
confidence: 99%
“…The largest RCT reporting data on more than 2,500 women, of which 471 had preexisting diabetes, did not demonstrate a beneficial effect of 60 mg/day of prophylactic aspirin initiated between 13 and 26 gestational weeks ( 117 ) ( Table 3 ). Meanwhile, a published conference abstract of a secondary analysis of this RCT ( 117 ) showed a beneficial effect of 60 mg/day aspirin initiated between 13 and 26 gestational weeks in the subgroup of women with preexisting diabetes and hypertension ( 121 ).…”
Section: Prophylactic Aspirin For Prevention Of Preeclampsiamentioning
confidence: 99%
“…Overall, the evidence from RCTs of a beneficial effect of routine prophylactic aspirin to prevent preeclampsia in women with preexisting diabetes is lacking ( 116 120 ), and a convincing effect has not been shown in real world cohort studies ( 24 , 102 , 121 , 126 , 127 ).…”
Section: Prophylactic Aspirin For Prevention Of Preeclampsiamentioning
confidence: 99%